Small punch creep property evaluation by finite element of Kocks-Mecking-Estrin model for P91 at elevated temperature. (December 2018) - Al-Abedy, H.K.; Jones, I.A.; Sun, W.
Highlights: The KME is viscoplastic model based on the dislocation density mechanisms. The multi-axial KME model is developed and written through UMAT. FE analyses is used to simulate the small punch creep behaviour of the P91 at 600 °C. The uniaxial tensile and conventional creep tests for the P91 at 600 °C are also simulated. A comparison of FE results with the corresponding experimental results is presented. Abstract: Small punch creep testing (SPCT) of thin disc specimens can be considered as a useful technique for determination of creep properties of exposed components of power generation and other thermal structures. Large viscoplastic strain in materials leads to damage and fracture which are examined from the microstructural aspects. In this work, the Kocks-Mecking-Estrin constitutive model is used to simulate the small punch creep behaviour of the P91 steel at 600 °C based on a full set of experimental results. An implicit computational algorithm is developed based on the radial return mapping approach. Finite element analyses of a small punch creep tests are carried out using ABAQUS software coupled with a UMAT material subroutine which has been developed by the authors. To demonstrate the applicability of the current model to P91 steel, the small punch creep test results are compared with the corresponding results from modelling using the UMAT code. In addition, a comparison of results of uniaxial tensile and creep tests for the P91 steel at 600 °C with the corresponding modelling results is also presented. The numerical results obtained have shown the model's versatility and good predictive capability for representing the visco-plasticity behaviour of the P91 steel at 600 °C.